Analysis of learning implementation plans (RPP) for prospective biology teacher students - Risa Audina; Risma Delima Harahap (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The purpose of this study is to analyze the learning implementation plan (RPP) for the independent learning curriculum of college student teacher candidates at Labuhan Batu University, in the microteaching course. The components of making the RPP for the independent learning curriculum consist of 3 components, namely: (1) learning objectives, (2) learning steps, (3) assessment. The data obtained were taken from RPP documents made by student teacher candidates in the microteching course. This study used a qualitative descriptive method, the instrument used was a checklist sheet about the suitability of the RPP components of the independent learning curriculum. The results of the analysis obtained the component of learning objectives with a score of 55.50% based on effectiveness during the learning process. The steps obtained a score of 75.50%, based on the arrangement made from the beginning to the end of the lesson. The last component studied is the assessment, the data obtained is 47.70%.Abstrak Tujuan dari penelitian ini untuk menganalisis rencana pelaksanaan pembelajaran (RPP) kurikulum merdeka belajar mahasiswa calon guru Universitas Labuhan Batu, pada mata kuliah microteaching. Adapun komponen dari pembuatan RPP kurikulum merdeka belajar terdiri dari 3 komponen yaitu: (1) tujuan pembelajaran, (2) langkah-langkah pembelajaran, (3) penilaian. Perolehan data diambil dari dokumen RPP yang dibuat oleh mahasiswa calon guru pada mata kuliah mikroteching.Penelitian ini menggunakan metode deskriptif kualitatif, instrumenyang digunakan adalah lembar checklist tentang kesesuain komponen RPP kurikulum merdeka belajar. Hasil analisis diperoleh komponen tujuan pembelajaran dengan skor 55.50% berdasarkan keefektifan selama proses pembelajaran berlangsung. Langkah-langkah diperoleh skor sebesar 75.50%, berdasarkan susunan yang dibuat dari awal hingga akhir pembelajaran. Komponen terakhir yang diteliti adalah penilaian, diperoleh data sebesar 47.70%.